2015
DOI: 10.1186/s13229-015-0026-z
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of local spontaneous brain activity and connectivity in adults with high-functioning autism spectrum disorder

Abstract: BackgroundPrevious autism research has hypothesized that abnormalities of functional connectivity in autism spectrum disorder (ASD) may vary with the spatial distance between two brain regions. Although several resting-state functional magnetic resonance imaging (rsfMRI) studies have extensively examined long-range (or distant) connectivity in the adult ASD brain, short-range (or local) connectivity has been investigated in less depth. Furthermore, the possible relationship between functional connectivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 93 publications
(122 reference statements)
9
53
1
2
Order By: Relevance
“…This further supported our findings that the bilateral pMTG was more vulnerable in both children and adults with ASD than in the TD group, which showed mainly hypoconnectivity with different brain regions. Our findings together with other studies [Itahashi et al, ; Scheel et al, ] highlighted the important role of the pMTG in the neuropathology of ASD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This further supported our findings that the bilateral pMTG was more vulnerable in both children and adults with ASD than in the TD group, which showed mainly hypoconnectivity with different brain regions. Our findings together with other studies [Itahashi et al, ; Scheel et al, ] highlighted the important role of the pMTG in the neuropathology of ASD.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, a study using a large sample size of individuals with ASD revealed diminished functional connectivity between the bilateral MTG and cerebellum [Ramos, Balardin, Sato, & Fujita, ]. Individuals with ASD not only exhibited local underconnectivity in the right pMTG, but also showed a significant association between disrupted local connectivity in this region and social interaction [Itahashi et al, ]. However, increased degree centrality in the left MTG [Lee, Park, James, Kim, & Park, ] and increased amplitude of low‐frequency fluctuation in the right MTG [Li, Rossbach, Jiang, & Du, ] were identified in individuals with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that bilateral middle temporal hypo-activation may be a general characteristic of language processing in ASD. This is noteworthy given the broad range of functions MTG plays in language processing, including auditory processing, semantic associations, and integration of words with meaning [Price, 2012].This is consistent with previous reports of MTG alterations in ASD, including decreased local connectivity [Itahashi et al, 2015] and altered morphology [Libero, DeRamus, Deshpande, & Kana, 2014]. However, MTG hypo-activation is seen in studies where task performance was intact, suggesting that the difference in language processing in ASD is not necessarily a weakness.…”
Section: Discussionsupporting
confidence: 83%
“…However it remains unclear how these results relate to patterns of atypical local connectivity reported using fMRI (e.g. Itahashi et al, 2015;Keown et al, 2013), and conflicting results are often reported. For example, You et al, (2013) used fMRI to compare functional connectivity during resting state and sustained attention in ASD and control groups.…”
Section: Task-related and Task-free Global Oscillatory Connectivity Dmentioning
confidence: 82%